Articulation and Transfer for Career and Technical Students: Best Practices for Dealing with Real and Perceived Barriers to Baccalaureate Degree Attainment for Applied Science Students. Issue 8 (3rd August 2017) - Fincher, Mark; Kelly, Chris; Harrison, Miranda; Harrison, Zachary; Hopson, Danielle; Weems, Selah
ABSTRACT: Community colleges produce large numbers of high quality graduates from career and technical programs. These programs are often of high academic rigor and quality. However, most universities view these Applied Associates of Science (AAS) as being terminal associate's degrees that are not appropriate for transfer. Regional accrediting standards are often cited as the reason for this differentiation. The reality is that institutional policies often simply dismiss AAS courses by their prefix to simplify the process. This study and presentation will explore the reality of what is allowed by accrediting bodies in transferring AAS courses and best practices for facilitating the maximum allowable course transfer.